Sequence organization and RNA structural motifs directing the mouse primary rRNA-processing event. - Craig, N (1991)
The first processing step in the maturation of mouse precursor rRNA involves cleavage at nucleotide ca. +650, at the 5' border of a 200-nucleotide region that is conserved across mammals and contains the sequences that direct the processing. To identify the relevant sequence elements, we used rRNAs with small internal mutations and short pre-rRNA substrates. Much of the region can be mutated without appreciable effect, but nucleotides +655 to +666 appear to be absolutely required and short segments surrounding +750 and +810 markedly stimulate processing. The minimal processing signal corresponds to rRNA nucleotides +645 to +672. Formation of a ribonucleoprotein complex of retarded electrophoretic mobility is evidently necessary but not sufficient for processing. Computer-assisted analysis suggested a phylogenetic- and mutant-supported secondary structure in which the minimal processing signal forms a stem with the +655 region in the loop, and there is a separate branched duplex containing the downstream stimulatory sequences. Use of antisense RNA, in trans and in cis, to sequester the +655 region in a duplex supported the hypothesis that this critical region was needed in a single-stranded conformation for processing and for specific complex formation.